2018
DOI: 10.1108/bjm-10-2017-0337
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable public value reporting of electric utilities

Abstract: Purpose The purpose of this paper is to investigate the status quo of Global Reporting Initiative (GRI)-based sustainable public value (SPV) reporting by electric utilities. Furthermore, the study attempts to find out whether a stock exchange listing and/or a public ownership are positively associated with electric utilities’ reporting regarding their contributions to a sustainable development (SD) or not. Design/methodology/approach An empirical analysis of sustainability reports published by electric utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…The exceptional role of CSR reporting in the energy sector [10,16] for information disclosure for the investors in the renewable energy sources that was highlighted in the other studies has been confirmed by the empirical study that was conducted in the Baltic States on the assessment of the CSR of energy utilities.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The exceptional role of CSR reporting in the energy sector [10,16] for information disclosure for the investors in the renewable energy sources that was highlighted in the other studies has been confirmed by the empirical study that was conducted in the Baltic States on the assessment of the CSR of energy utilities.…”
Section: Discussionmentioning
confidence: 76%
“…Corporate social responsibility (CSR) allows utilities to deal with the challenges of sustainable development, including climate change, and implement sustainable business practices and CSR reporting [10]. The analysis of CSR practices of energy utilities in various world countries (Brazil [7,8], Poland [9], The US [10,11], China [12,13], India, and Japan [14], and groups of countries [15][16][17][18]), indicated the importance of CSR for dealing with the major risks and challenges that the energy sector is facing, i.e., corruption risks [19][20][21][22] and other important drivers like competition [36][37][38], reputation [40], customers loyalty [41][42][43][44][45][46][47][48][49][50][51][52][53], and policies [39,[53][54][55], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the last decades and due to globalization, climate change, increasing environmental pollution and the scarcity of resources, companies experienced increased stakeholder pressure to disclose information not only on financial (economic) performance but also on ecological and social aspects (Boiral et al, 2019;Sartori et al, 2017;Garcia et al, 2016;Fernandez-Feijoo et al, 2014) along the Triple-Bottom-Line (TBL) dimensions (Elkington, 1997). As a reaction and to gain, maintain or regain legitimacy and reputation (Deegan, 2014), sustainability reporting is becoming an institutionalized practice, especially in private and stock-exchange listed companies (Traxler and Greiling, 2018;Brown et al, 2009). Studies show that the public and the non-profit sectors are lagging behind implementing and disclosing TBL-information in sustainability reports (SR) (Traxler and Greiling, 2018;Lock and Seele, 2016;Greiling et al, 2015a, b).…”
Section: Motivation and Research Objectivesmentioning
confidence: 99%